The contemporary development of netball in Singapore - Divyashree Balakrishnan (2016)
In Singapore, netball was presented with the status of “merit” sport only in 2002. However, it was as early as 1962, when the body organizing the sport was officially recognized as an association. Despite its long maturation process and fruitful development as a major female team sport, few academic works have critically examined the place of netball in the development of sport in Singapore in the contemporary field. Leadership in organization has been credited as a critical component for the commendable sports program we observe today, yet the women athletes and coaches inevitably make a significant contribution to the growing success of the sport.